KATA GANTI ORANG DALAM NOVEL THE COLLECTOR KARYA JOHN FOWLES - LUMI, ALICIA FEBRIANI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT   The title of this research is "Personal Pronouns in The Novel The Collector by the John Fowles". The objectives of this research are to identify, to classification and to analyze the form of personal pronouns.  The data are collected by focusing on the writer presents her novel by using personal pronouns. the theory  used in this research is taken from Frank (1972). The problem of the research: what are the personal pronouns in term of form and function in the novel The Collector by John Fowles. I, she, we, they can be subjects of a verb. Example : I saw it. He knows you. They live near here. Coplements of the verb to be : example it is I. Me, him, her, us, them can be direct objects of a verb. Example : I saw her. Tom likes them. Those concepts above will be used for identifying and analyzing data.  The result shows that the forms of personal pronouns are found in the novel The Collector by John Fowles. The result shows that there are personal pronouns is a word used in the place of a noun either persons or things. The function of perosnal pronoun is a subject, object possessive adjective and possessive in the sentence.   Keywords : Personal Pronouns, Novel : The Collector